THE EFFECTS OF DONOR FUNDING ON THE PERFORMANCE OF SEXUAL REPRODUCTIVE HEALTH NGOS IN MOMBASA COUNTY - Gachenge, Lydiah; Githui, Thomas; Gathaiya, Robert (International Journal of Finance, 2021)
Purpose: Local Non-Governmental Organizations (NGOs) play crucial role in uplifting livelihoods and overall economic development in Kenya. However, several local NGOs have experienced dwindling performance as a result of insufficient donor funding. It is in this vein that the current study assessed the effects of donor funding on the organizational performance of local sexual reproductive health NGOs in Mombasa County. The specific study objectives included; to establish the effect of availability of donor funds, funds management, and capacity building on the performance of local NGOs. Methodology: The study adopted a descriptive survey research design while the target population was all the employees of sexual reproductive health NGOs in Mombasa County. The study used simple random sampling technique. A structured questionnaire was self-administered to all employees of the 14 NGOs. The study utilized descriptive statistics and multiple regression analysis. Diagnostic tests such as normality and multicollinearity were used. Results: The research found that funds' management, funds' availability, capacity building, and government policies had positive relationship with NGOs project performance. The study concludes that NGOs had various sources of funding. It concludes that the NGOs ensured funds' management by employing qualified accounting staff, embracing openness for regular donor evaluations, ensuring financial disclosures to stakeholders. The study concludes that NGOs' staff had adequate experience in running projects. It was concluded that there was no level business environment for local NGOs, the available government NGO operation policies were unfriendly and the Co-ordination Act needed improvement. Unique contribution to theory, policy and practice: The study recommends that all NGOs should continue sourcing for multiple reliable funders. The study recommend that all NGOs should uphold proper planning for finances, monitoring, evaluation, and budgeting control to ensure accountability to promote successful completion of projects. The study recommends that NGOs' staff should be subjected to regular timely task-oriented training.